Modern Data Visualization with R - Kabacoff, Robert (Boca Raton : CRC Press/Taylor & Francis, 2024)
Modern Data Visualization with R describes the many ways that raw and summary data can be turned into visualizations that convey meaningful insights. It starts with basic graphs such as bar charts, scatter plots, and line charts, but progresses to less well-known visualizations such as tree maps, alluvial plots, radar charts, mosaic plots, effects plots, correlation plots, biplots, and the mapping of geographic data. Both static and interactive graphics are described and the use of color, shape, shading, grouping, annotation, and animations are covered in detail. The book moves from a default look and feel for graphs, to graphs with customized colors, fonts, legends, annotations, and organizational themes.
Includes bibliography and index.
Keywords: Data visualization; ggplot2.; Graphics; Multivariate Graphs